1995
DOI: 10.1111/j.1365-2249.1995.tb02295.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the IL-1 cytokine network in keratinocytes by intracellular IL-1α and IL-1 receptor antagonist

Abstract: SUMMARYThe IL-I cytokine network in epidermal cells was studied in vitro, using the spontaneously transformed HaCAT human keratinocyte line. Intracellular (ic) IL-la and IL-1 receptor antagonist protein (IL-lRa) following cell lysis were readily identified assayed using a capture ELISA; whereas in culture supematants IL-lRa was not detected, and IL-Uv was present at only very low levels. Confiuent cultures of HaCAT cells were shown to provide optimal conditions for the study, since confluence increased the icI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…IL1α is produced in large amounts by keratinocytes and stored intracellularly . As in the psoriatic epidermis keratinocyte turnover is augmented and the differentiation programme is disturbed, the keratinocytes do not have the capacity to synthesize and stock IL1α at levels characteristic of homeostatic human epidermis, resulting in reduced IL1α levels in lesional skin and SC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL1α is produced in large amounts by keratinocytes and stored intracellularly . As in the psoriatic epidermis keratinocyte turnover is augmented and the differentiation programme is disturbed, the keratinocytes do not have the capacity to synthesize and stock IL1α at levels characteristic of homeostatic human epidermis, resulting in reduced IL1α levels in lesional skin and SC.…”
Section: Discussionmentioning
confidence: 99%
“…64 IL1a is produced in large amounts by keratinocytes and stored intracellularly. 65 As in the psoriatic epidermis keratinocyte turnover is augmented and the differentiation programme is disturbed, 66 the keratinocytes do not have the capacity to synthesize and stock IL1a at levels characteristic of homeostatic human epidermis, resulting in reduced IL1a levels in lesional skin and SC. The term 'molecular scars' has been introduced for biomarkers not returning to homeostatic levels in clinically normal skin of patients with psoriasis who have undergone successful drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of K17 in Gli2 tg skin correlates with a marked reduction in Th1- and Th17-related markers and induction of Th2-related markers ( Table 1 ), many of which are prominently expressed by skin keratinocytes themselves. Expression of IL-1β, a keratinocyte mitogen 20 , is ~10 fold higher in Gli2 tg compared to Gli2 tg /K17 −/− skin ( Table 1 ). Immunostaining shows that IL-1β epitopes are strongly expressed in the skin epithelium ( Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Cytokine production. HaCaT cells were cultured in 24-well plate at a density of 2×10 5 cells/well in 500 μL of DMEM medium (24 h, 37°C) to reach confluence (Phillips et al, 1995), and treated with dendrimers at non cytotoxic 0.1 or 1.0 µM concentrations with or without stimulants. The following stimulants were used: E. coli LPS strain 0111: B4 in PBS at a final concentration of 100 ng/ml, PMA diluted in DMSO at a final concentration of 50 ng/mL, and E. coli GroEL (Hsp60) protein at a final concentration of 1 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Immunosuppressive and anti-inflammatory properties of various types of dendrimers have been characterized (Ilinskaya & Dobrovolskaia, 2014). However, comparative studies of the IL-1α expression, a basic keratinocyte proinflammatory cytokine (Phillips et al, 1995;Feldmeyer et al, 2010), in normal human epidermal keratinocytes (NHK), spontaneously immortalized HaCaT and transformed by human papillomavirus (HPV) EK 16 and EK18 lines of keratinocytes revealed that they reacted differently after UVB-irradiation and/or treatment with CsA (Marionnet et al, 1997). Similarly, Pastore and others (Pastore et al, 2011) had documented that NHK and HaCaT responded by different chemokine production under treatment with plant polyphenols at the constitutive, UVA-, LPS-, or TNF-α-induced inflammatory responses.…”
Section: Production Of Proinflammatory Cytokines Il-1α and Tnf-αmentioning
confidence: 99%